2016
DOI: 10.1097/rlu.0000000000001131
|View full text |Cite
|
Sign up to set email alerts
|

Increased 18F-FDG Uptake Associated With Gastric Banding Surgical Mesh on PET/CT

Abstract: Surgical mesh was used in the 1980s and early 1990s for vertical banded gastroplasty as treatment for morbid obesity. This procedure was replaced by the more popular laparoscopic gastric banding in the mid-1990s. Surgical mesh, commonly used in hernioplasty, has been associated with increased F-FDG uptake related to an inflammatory foreign body reaction and is a known cause of false-positive PET scans. We present a case of increased F-FDG uptake related to surgical mesh in a patient who had undergone vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recently, a study from Chism and coworkers 32 reported an increased 18 F-FDG uptake related to surgical mesh in a patient who had undergone vertical banded gastroplasty, corresponding to false-positive PET scan.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, a study from Chism and coworkers 32 reported an increased 18 F-FDG uptake related to surgical mesh in a patient who had undergone vertical banded gastroplasty, corresponding to false-positive PET scan.…”
Section: Reviewmentioning
confidence: 99%